2014
DOI: 10.1038/ncomms6296
|View full text |Cite
|
Sign up to set email alerts
|

Satellite telemetry and social modeling offer new insights into the origin of primate multilevel societies

Abstract: Multilevel societies (MLS), in which polygynous reproductive units are nested in a larger social matrix, represent a highly complex social system documented only in a small number of mammalian species. Using long-term behavioural data, satellite telemetry and social network analysis, we present a new framework for understanding the function and social dynamics of the golden snub-nosed monkey MLS. Here we show that several one-male units form a cohesive breeding band that associates with one or more all-male un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
143
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 58 publications
1
143
0
Order By: Relevance
“…We only recorded behavioural patterns outside the provisioning periods. Moreover, social structure, size, OMU composition and mating behaviour of our study troops were similar to those reported in nonprovisioned troops of this species [Tan et al, 2007;Qi et al, 2014].…”
Section: Food Provisioningsupporting
confidence: 85%
“…We only recorded behavioural patterns outside the provisioning periods. Moreover, social structure, size, OMU composition and mating behaviour of our study troops were similar to those reported in nonprovisioned troops of this species [Tan et al, 2007;Qi et al, 2014].…”
Section: Food Provisioningsupporting
confidence: 85%
“…but these methods are time consuming and provide irregular and sometime biased information (e.g., when one individual is more easily seen or recognized than another; Whitehead, 2008). More recently, the development of GPS collars has provided new ways to gather relatively large amounts of data over substantial periods of time (e.g., Patzelt et al, 2014;Qi et al, 2014). However, GPS techniques have a relatively poor spatial resolution and can only be used to track the movements of groups of individuals (between-group SNA), but not the proximity of individuals within groups.…”
mentioning
confidence: 99%
“…Each unit contains, on average, 9 monkeys; a resident (or leader) adult male, 2-5 adult females and offspring of varying ages Qi et al, 2009]. Maturing animals often emigrate from their natal groups, and males may join all-male units, several of which may coalesce into an all-male band [Qi et al, 2014[Qi et al, , 2017. Breeding bands consist of an aggregation of several 1-male units, and all-male bands consist of an aggregation of several all-male units.…”
Section: Introductionmentioning
confidence: 99%